Sexual violence policies and sexual consent education at Canadian post-secondary institutions - Tavcer, D. Scharie (Routledge focus, 2023)
"This book is the culmination of three years of research into sexual violence policies and sexual consent education at post-secondary institutions across Canada. The prevalence of sexual violence has not changed in more than 30 years, and its reporting to police or school authorities has only waxed and waned over those years. In response, this book asks what can be done differently to reduce the number of victims and potential perpetrators? The book provides an environmental scan of over 120 post-secondary institutions (PSIs) across Canada as well as a deeper analysis of 7 PSIs that also include student and staff experiences and opinions. The three-year research project employed various phases to capture over 160 student voices and over 20 sexual violence staff and subject experts. Subject experts and students were also involved in review the draft iterations of the proposed sexual consent education module. This book delivers readers with a broad-brush approach to understanding the landscape of sexual violence prevention and education services at PSIs across Canada. It provides a narrowed focus on 7 PSIs where student and staff survey responses and interviews provide positionality in response to the available literature. The book concludes with our proposed sexual consent education module, including its strengths and limitations, as a point of discussion for PSIs to include the online module into their sexual violence prevention education repertoire. This book is intended for post-secondary audiences in Canada, North America, and elsewhere - for undergraduate and graduate students and faculty, staff, and administrators - where it is crucial to consider ways to address its prevalence and the ways we can incorporate prevention education into our campus communities"--